KAJIAN TEOLOGI TENTANG PERSEPULUHAN DITINJAU DARI 2KORINTUS 9:6-10 - Kurniawan, Ernest; Darmawan, Darmawan; Kasianus, Andre (Jurnal Teologi Biblika, 2025)
The pros and cons regarding tithing have recently emerged and are always an interesting topic of discussion. There are those who claim that tithing was only valid during the old covenant, so it is no longer relevant in this postmodern era. In addition, recently there has been negative news on social media about servants of God who have abundant wealth, wearing luxury items allegedly from receiving the congregation's tithes. Also, economic conditions in recent times have become increasingly difficult, wars have emerged, disasters have occurred, crime related to finances has become increasingly widespread and many people are worried and love money more and more. On the other hand, God's work on earth still requires money. This journal is written to examine the concept of tithing and its relationship to the Word in 2 Cor 9:6-10, using descriptive qualitative methods. The findings from the research are that tithing is closely related to a heart that is obedient and loves God.